2015
DOI: 10.7863/ultra.15.14.10045
|View full text |Cite
|
Sign up to set email alerts
|

A Model Using Texture Features to Differentiate the Nature of Thyroid Nodules on Sonography

Abstract: Gray-level co-occurrence matrix texture features extracted from sonograms of thyroid nodules coupled with a logistic model are useful for differentiating between benign and malignant thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…The quality of the included studies is summarized in online supplementary Table 2. The risk of bias from patient selection was judged to be high or unclear in 13 of the included studies: 4 studies limited the nodule size within a certain scope [16,17,21,25]; 5 studies excluded difficult-to-diagnose nodules [15,[25][26][27]31]; and 4 studies were unclear about whether there were selected co-horts and inappropriate exclusions [14,19,23,29]. The risk of bias from the reference standard was considered to be unclear in 2 of the included studies [14,23].…”
Section: Methodological Quality Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The quality of the included studies is summarized in online supplementary Table 2. The risk of bias from patient selection was judged to be high or unclear in 13 of the included studies: 4 studies limited the nodule size within a certain scope [16,17,21,25]; 5 studies excluded difficult-to-diagnose nodules [15,[25][26][27]31]; and 4 studies were unclear about whether there were selected co-horts and inappropriate exclusions [14,19,23,29]. The risk of bias from the reference standard was considered to be unclear in 2 of the included studies [14,23].…”
Section: Methodological Quality Of the Included Studiesmentioning
confidence: 99%
“…The risk of bias from patient selection was judged to be high or unclear in 13 of the included studies: 4 studies limited the nodule size within a certain scope [16,17,21,25]; 5 studies excluded difficult-to-diagnose nodules [15,[25][26][27]31]; and 4 studies were unclear about whether there were selected co-horts and inappropriate exclusions [14,19,23,29]. The risk of bias from the reference standard was considered to be unclear in 2 of the included studies [14,23]. The risk of bias from flow and timing was considered to be high or unclear in 7 of the included studies, and these studies adopted pathological examination, fine needle aspiration, and ultrasound as reference standards for diagnosing benign nodules [19,22,25,27,28,30,31].…”
Section: Methodological Quality Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Previous studies have reported that histograms and texture analyses of US are useful for differentiating benign and malignant thyroid nodules. [16][17][18][19][20][21] To our knowledge, there have been no published studies aimed at identifying the presence of BRAF mutation using radiomics features of US.…”
mentioning
confidence: 99%